Perbaikan dan Proteksi Pondasi Tiang Dermaga Dengan Metode Pile Encapsulation - Sulardi, Sulardi (Jurusan Teknik Sipil, 2018)
Problems encountered in this research is the occurrence of foundation damage pier dock building PT. Reliance Refinery in Gujarat Province of India resulting in dock structure under sub standard condition, unsafe condition and at any time dock structure may experience colapse. The specific point of this problem is the dock building is supported by a 120 cm diameter pile foundation with a height of 14 meters above ground level and over 200 meters towards the Indian Ocean. The purpose of this study is to provide an overview of how the specifications of materials, work equipment and methods of implementing the repair of damaged pier building foundations. Improvement using pile encapsulation method is by cleaning the damaged piling surface with water jeting and mechanical, installing FRP jacketing cover and grouting with underwater material specifications epoxy grout. The improvement results show the epoxy grout and FRP jacket bonding well to the existing piling surface. This repair method is proven to improve the damage of the piling and protect the piling against corrosion, abrasion, scouring and mechanical impact. These improvements have been replicated to address similar problems in Canada, Australia, Singapore and Indonesia.